Letter (copy) : "Save the Basque Children" Fund - Tewson, Vincent
037-0103-001 HVT/FC/606 Secretary's. 29th June, 1937. Mr. W. Hughes, The Dundee Trades and Labour Council, 8, Stirling Terrace, DUNDEE. Dear Mr. Hughes, "SAVE THE BASQUE CHILDREN" FUND. Further to my letter of the 22nd instant I have been in touch with the office of the National Committee for the Care of Basque Children in regard to your request for the names of children who might be regarded as being "adopted" by your Organisation. I am informed that there is a Mrs. Chapman of 94 Ellengowan Drive, Dundee, who has been in touch with the National Committee in regard to the possibility of Dundee adopting a number of children. It occurs to me that perhaps this scheme might be of particular interest to you and if you were to have a word with Mrs. Chapman you could see how the scheme fitted in with your desires. After you have have had a consultation locally on this matter perhaps you would write me again. Yours sincerely, Assistant Secretary. 292/946/37/103